Dynamic amplification factors for highway bridges: State-of-the-art - Arun, S.; Menon, Devdas; Prasad, A. Meher (Journal of Structural Engineering, 2024)
Dynamic effects induced by moving traffic over bridges are traditionally accounted for in design by an equivalent static treatment through the use of amplification factors or impact factors. Though the various bridge design standards around the world specify these factors either as a function of bridge span or fundamental frequency, many other parameters are found to have a strong influence. The topic has been well researched in the past and still continues to be an active area of research, with the renewed interest propelled by the increased awareness about the economy achieved by the use of proper bridge load models. This paper reviews some major factors influencing the dynamic amplification factors of highway bridges and the current research directions in estimation of the same.